A study of information technology adoption in high education institutions in the state of Kuwait - Aldaihani, Adel Rashed (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2020)
The world scenario has been changed by Information and Communication Technology (ICT), and many factors including new opportunities, fast-growing businesses, technological changes, and challenges have forced every part of the world to produce self-regulating and to pre-found skilled oriented individual. Driven by this compulsion the high education institutions (HEI) around the globe are integrating ICT tools and utilizing the latest technologies in order to provide quality education to their citizens. In this regard Ministry of Education (MOE) Kuwait has launched many plans and invested a lot in the implementation of technology in HEIs. HEIs mainly consists of Universities. There is no comprehensive study in order to assess the adoption of ICT in the universities by all main stakeholders of Kuwait as well as no empirical study have been conducted on the overall effectiveness of ICT in the HEI (s). The effectiveness of any new technology depends upon acceptance and proper utilization of technology by all stakeholders. Subsequently, realizing the importance of ICT availability and success in all parts of society, this research aimed to understand, investigate, explore, and assess the ICT adoption in the universities of Kuwait. Meanwhile, in order to assess the adoption and utilization of ICT by students and academicians in their daily work, this research proposed a model by adopting variables Performance Expectancy (PE), Effort Expectancy (EE), Social Influence (SI), Facilitating Conditions (FC), Behavioural Intention (BI), and Use Behaviour (UB) from Unified Theory of Acceptance and Use of Technology (UTAUT) with external factors such as Compatibility, Perceived Needs, Self-efficacy, Complexity, and Culture. The proposed research model was validated through Structural Equation Modeling (SEM) using Smart-PLS software. A total of 401 were collected through stratified random & purposive sampling methods using five-point Likert scale. Research findings indicate that nine out of eleven hypotheses were found to be statistically significant. Moreover, BI, compatibility, PE, and FC were found most significant factors that influence UB to accept ICT. Results further revealed that 54.1% variance in BI and 45% in UB is explained. Besides, many theoretical and methodological contributions for academicians, this research seizes many significant practical and theoretical implications for researchers, practitioners, information, and many other governmental and non-governmental institutions.